Modification of the Weighted Product Model: Towards a Fairer and More Rational Ranking - Adhie Thyo Priandika; Permata Permata; Sumanto Sumanto; Setiawansyah Setiawansyah (Faculty of Science and Technology, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2026)
The weighted product (WP) method is one of the popular methods in decision support systems (DSSs) due to its simplicity, calculation efficiency, and ability to handle various types of criteria with different weights. This research proposes a modification to the WP model designed to enhance fairness and rationality in the ranking process of alternatives. Therefore, a modified approach, Weighted Product with Averaging and Mean-Normalized Evaluation (WP-A), is adopted by integrating objective weighting methods and more adaptive normalization, so that each criterion can be evaluated proportionally. The supplier selection case study is used to test the effectiveness of the proposed model by comparing it with other MCDM methods. The results of the study show that the WP-A method produces more consistent results and has a stronger correlation with other methods, as indicated by Spearman's correlation test, with a value of 0.9828, indicating a very strong level of consistency with the reference rankings. The main contribution of this research is to provide a new framework for the development of the WP method so that it can be relied upon to support a more transparent and objective decision-making system.